Determination of Oocyte-Manipulation, Zygote-Manipulation, and Genome-Reprogramming Effects on the Transcriptomes of Bovine Blastocysts - Min, Byungkuk; Park, Jung S.; Kang, Yong-Kook (Frontiers in Genetics, 2018)
Somatic cell nuclear transfer (scNT) embryos suffer from damage caused by micro-operation (manipulation) and inefficient genome reprograming that hinder their normal development at different levels and in distinct ways. These two effects are inseparable in the nature of the scNT embryo, although methods to separately measure them are needed to improve scNT technology and evaluate incoming reprogramming tools. As an attempt to meet these demands, we made bovine sham nuclear-transfer (shNT) blastocysts, special embryos made with a standard nuclear-transfer procedure at the zygote stage, while retaining an intact genome. We compared their transcriptomes with those of other blastocysts derived by in-vitro fertilization (IVF) or scNT. Correlation analysis revealed a singularity of shNT blastocysts as they separately gathered from the others. Analysis of developmentally important genes revealed that, in shNTs, the stemness-associated differentially expressed genes (DEGs), including OCT4, were mostly underrepresented. Overrepresented epi-driver genes were largely associated with heterochromatin establishment and maintenance. By multilateral comparisons of their transcriptomes, we classified DEGs into three groups: 561 manipulation-associated DEGs (MADs) common to shNTs and scNTs, 764 donor genome-associated DEGs (DADs) specific to scNTs, and 1743 zygote manipulation-associated DEGs (zMADs) specific to shNTs. GO enrichment analysis generated various terms involving “cell-cell adhesion,” “translation,” and “transcription” for MADs and “cell differentiation” and “embryo implantation” for DADs. Because of the transcriptomic specificity of shNTs, we studied zMADs in detail. GO enrichment analysis with the 854 zMADs underrepresented in shNTs yielded terms related to protein and mitochondria homeostasis, while GO enrichment analysis of 889 shNT-high zMADs yielded terms related to endoplasmic reticulum stress and protein transport. We summarized the DEGs, which, with further investigation, may help improve our understanding of molecular events occurring in cloned embryos and our ability to control clonal reprogramming.